Impact of gut microbiota on endometriosis: linking physical injury to mental health - Li Yuanyue; Li Yuanyue; Li Yuanyue; Hu Qian; Hu Qian; Liu Ling; Yang Liufeng; Yang Liufeng; Ge Jing; Ge Jing; Wu Xiaomei; Wu Xiaomei (Frontiers in Cellular and Infection Microbiology, 2025)
Endometriosis is widely recognized as a chronic, inflammatory, and heterogeneous condition that can manifest in various anatomical locations within females. It is marked by estrogen-driven cycles of bleeding, cell proliferation, and fibrosis involving ectopic endometrial glands and stroma cells located outside the uterus. The limited understanding of its etiology and complex pathogenesis has created obstacles in achieving early diagnosis and developing effective treatments with minimal side effects. Consequently, endometriosis requires more in-depth research to unravel its pathogenesis. The gut microbiota, a key player in chronic diseases, significantly influences bodily metabolism and immune regulation. Emerging evidence links the gut microbiota to inflammation, estrogen metabolism, and immune responses—key factors in the onset and progression of endometriosis. This review examines the various mechanisms through which endometriosis and the gut microbiota interact, aiming to inspire new strategies for preventing and early treating endometriosis.